Systemic Administration of Propentofylline, Ibudilast, and (+)-Naltrexone Each Reverses Mechanical Allodynia in a Novel Rat Model of Central Neuropathic Pain - Ellis, Amanda (2014)
Central neuropathic pain (CNP) is a debilitating consequence of central nervous system (CNS) damage for which current treatments are ineffective. To explore mechanisms underlying CNP, we developed a rat model involving T13/L1 dorsal root avulsion. The resultant dorsal horn damage creates bilateral below-level (L4-6) mechanical allodynia. This allodynia, termed spinal neuropathic avulsion pain (SNAP), occurs in the absence of confounding paralysis. To characterize this model, we undertook a series of studies aimed at defining whether SNAP could be reversed by any of 3 putative glial activation inhibitors, each with distinct mechanisms of action. Indeed, the phosphodiesterase inhibitor propentofylline, the macrophage migration inhibitory factor (MIF) inhibitor ibudilast, and the toll-like receptor 4 (TLR4) antagonist (+)-naltrexone each reversed below-level allodynia bilaterally. Strikingly, none of these impacted SNAP upon first administration but required 1–2 wk of daily administration before pain reversal was obtained. Given reversal of CNP by each of these glial modulatory agents, these results suggest that glia contribute to the maintenance of such pain and enduring release of MIF and endogenous agonists of TLR4 is important for sustaining CNP. The markedly delayed efficacy of all 3 glial modulatory drugs may prove instructive for interpretation of apparent drug failures after shorter dosing regimens.